The inﬂuence of group decision making on search behavior - Destan, Cavit Görkem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
We study a multi-agent search problem within an experimental framework. Two agents search separately with their own search costs for a reward that is common for both which can create a free-rider problem. In general, we found that behavior of the agents are consistent with the predictions of the theory. Even though the results slightly moved away from the optimal compared to individual search problem, in group search problem strategies of subjects are still substantially close to the best-response. Moreover, we controlled for the personality traits, gender, risk attitude and background in economics. However, we did not ﬁnd any signiﬁcant effect of these on optimal decision rate or free-ride.
Keywords: Group decision making.